Early effector maturation of naïve human CD8+ T cells requires mitochondrial biogenesis. Issue 10 (7th August 2018) - Fischer, Marco; Bantug, Glenn R.; Dimeloe, Sarah; Gubser, Patrick M.; Burgener, Anne‐Valérie; Grählert, Jasmin; Balmer, Maria L.; Develioglu, Leyla; Steiner, Rebekah; Unterstab, Gunhild; Sauder, Ursula; Hoenger, Gideon; et al.
Abstract: The role of mitochondrial biogenesis during naïve to effector differentiation of CD8 + T cells remains ill explored. In this study, we describe a critical role for early mitochondrial biogenesis in supporting cytokine production of nascent activated human naïve CD8 + T cells. Specifically, we found that prior to the first round of cell division activated naïve CD8 + T cells rapidly increase mitochondrial mass, mitochondrial respiration, and mitochondrial reactive oxygen species (mROS) generation, which were all inter‐linked and important for CD8 + T cell effector maturation. Inhibition of early mitochondrial biogenesis diminished mROS dependent IL‐2 production – as well as subsequent IL‐2 dependent TNF, IFN‐γ, perforin, and granzyme B production. Together, these findings point to the importance of mitochondrial biogenesis during early effector maturation of CD8 + T cells. Abstract : Activation induced mitochondrial biogenesis is important for mROS dependent IL‐2 production in naïve CD8 + T cells. Autocrine IL‐2 signaling is critical for subsequent TNF, IFN‐γ, perforin and granzyme B production. Thus, mitochondrial biogenesis is a requirement for early effector maturation of naïve CD8 + T cells.